The theology of Jonathan Edwards : a reappraisal - Cherry, Conrad, 1937-; Stein, Stephen J. (Bloomington, Ind. : Indiana University Press, 1990)
" ... The Edwards of Cherry sits for a[n] ... intellectual portrait, done with concepts as colors and with reason as the brush. It is a ... picture ... faithfully and competently drawn."--New York Times Book Review, 1967" ... this is a very good book ... It stresses the integral relationship of heart and mind, intellect and will throughout Edwards ... an important book ... required reading for any student of Edwards."--Church History, 1967
Reprint. Originally published: Garden City, N.Y. Doubleday, 1966.
Includes bibliographical references and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Edwards, Jonathan, -- 1703-1758.; Edwards, Jonathan, -- 1703-1758; Christianity; Religion; Philosophy & Religion; RELIGION -- Christianity -- General; RELIGION -- Christian Theology -- Systematic